Revue de la jurisprudence récente du comité de discipline de l’Association des intermédiaires en assurance de personnes du Québec - Beaudoin, Anne-Marie (Assurances, 1996)
In conformity with the Act Respecting Market Intermediaries, AIAPQ is responsible to enforce discipline among its 13,000 agents and brokers. On February 1, 1996, Mrs. Anne-Marie Beaudoin, Attorney, carried out a review of the most recent jurisprudence of the Disciplinary Committee which has not been published otherwise. You will discover new judgments relating to the Act Respecting Market Intermediaries and its applicable regulations. You will also find decisions concerning practise conditions such as duplication, criminal act and bankruptcy. Replacement procedure and ethical rules such as funds appropriation are also considered. Finally, an analysis of sanctions as well as their causes complement this jurisprudence review.